DETECTION OF Leptospira spp. AND Brucella abortus ANTIBODIES IN FREE-LIVING JAGUARS (Panthera onca) IN TWO PROTECTED AREAS OF NORTHERN PANTANAL, BRAZIL - ONUMA, Selma Samiko Miyazaki; KANTEK, Daniel Luis Zanella; CRAWSHAW JÚNIOR, Peter Gransden; MORATO, Ronaldo Gonçalves; MAY-JÚNIOR, Joares Adenilson; MORAIS, Zenaide Maria de; FERREIRA NETO, José Soares; AGUIAR, Daniel Moura de (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
This study aimed to assess the exposure of free-living jaguars (Panthera onca) to Leptospira spp. and Brucella abortus in two conservation units in the Pantanal of Mato Grosso, Brazil. The presence of antibodies in blood samples of eleven jaguars was investigated using autochthonous antigens isolated in Brazil added to reference antigen collection applied to diagnosis of leptospirosis by Microscopic Agglutination Test (MAT). The Rose Bengal test was applied for B. abortus antibodies. Two (18.2%) jaguars were seroreactive for the Leptospira spp. antigen and the serovar considered as most infective in both animals was a Brazilian isolate of serovar Canicola (L01). All jaguars were seronegative for B. abortus. These data indicate that the inclusion of autochthonous antigens in serological studies can significantly increase the number of reactive animals, as well as modify the epidemiological profile of Leptospira spp. infection.